Hostile, Quick-Tempered, and Exposed to Dangerous Environments: exploring the Link Between Temperament and the Street Code Adherence - Wolff, Kevin T. (Crime & delinquency, 2023)
Although Elijah Anderson?s code of the street thesis has received a great deal of scholarly attention, fewer studies have examined the characteristics associated with its adoption. Existing evidence is supportive of Anderson?s initial observations, however, less is known about the association between personality and emotional characteristics and adopting street code norms. The current study assesses the role of DeLisi and Vaughn?s difficult temperament index in the adoption of the street code among a sample of juvenile justice-involved youth. Results indicated youth with more difficult temperaments, characterized by lower levels of effortful control and higher levels of negative emotionality, were more likely to report greater street code adherence. Implications for juvenile justice policy and future research are discussed.